Studies on the fertility of sheep in height - San Martín, Mauricio (1942)
The author studies the semen of the rams in its known characteristics, and states the differences found at 4500 mts. of altitude. The very well know fact of reduced birth rate (50 to 60 % versus 100 % at sea level), is due to several factors : The deviations of pH are greater than at sea level. The number of spermatozoids is rather high, but there are young forms frequently seen, with a decrease of their mobility, as well as the presence of white blood cells, epithelial cells, etc. In fact he founds only 26 % of 58 supposedly normal rams, which could be considered suited for reproduction. By means of artificial insemination, and using selected males, he obtained 86,4 % of fertility, the result being very impressive as the ewes served were those so called "machorras" (infertiles). This paper proves, therefore, that the reduced birth rate of sheep at high altitude, is due to a diminishing ability of fecundation in the semen. The author gives suggestions for increasing fertility in high altitude rams. From the scientific as well as from industrial point of view, the results are very encouraging.